An account on the Phaneropterinae (Tettigonioidea: Tettigoniidae) from the highlands of western Sabah - Tan, Ming Kai; Liu, Chunxiang; Ingrisch, Sigfrid; Japir, Razy; Chung, Arthur Y.c. (Zootaxa, 2024)
Based on an orthopteran survey in different parts of western Sabah, a total of 24 species from 16 genera are reported here, i.e., three species from one genus of Elimaeini, 14 species from nine genera of Holochlorini and three species from two genera of Mirolliini. Among them, four species of Holochlora new to science are described from Mount Trus Madi: Holochlora bulbosa Tan, Liu & Ingrisch, sp. nov., Holochlora falcata Tan, Liu & Ingrisch, sp. nov., Holochlora bispinosa Tan, Liu & Ingrisch, sp. nov. and Holochlora cratera Tan, Liu & Ingrisch, sp. nov. One new genus of Holochlorini is described from Mount Trus Madi: Pulchrapsyra cyanea Tan, Liu & Ingrisch, gen. et sp. nov. One species of Deflorita (Separita) new to science from Mount Trus Madi is described: Deflorita (Separita) extensa Tan, Liu & Ingrisch, sp. nov.